Failure Analysis of a Drop Tested Wall-Mounted Air Conditioner Indoor Unit: Simulation and Experimental Analysis - YAYLA, PAŞA (GAZI UNIV, 2020)
Dynamic behaviour of a wall-mounted air conditioner indoor unit is analysed under drop impact condition. For simulation analysis, a finite element analysis code, known as Ansys Autodyn, is used. Physical drop tests are performed according to ASTM D5276 and ASTM D880 standards and strain gauges are used to measure the effective strains by attaching to specific areas subjected to excessive deformation. By recording drop test with high speed camera, the impact contact duration is also detected. By comparing experimental and numerical results, the validation of finite element analysis is performed. Product improvements are made for the damaged areas and validated by drop test. Conducting physical drop tests with strain gauges together with finite element analysis decreases product development lead time, reduces development costs and eliminates the product's potential risks in advance. The approach presented with this work can be a reference guide for assessing the dynamic response of impact sensitive home and industrials applicants.
Keywords: Drop test; Failure analysis; Finite element method; Air conditioner unit; Packaging; PACKAGE; DESIGN